The avocado : botany, production, and uses. - Carrillo, Daniel; Schaffer, Bruce; Wolstenholme, B. N. (B. Nigel); Whiley, A. W. (Anthony William) (CAB International, 2024)
"Avocado production is continuing to expand, and is expected to reach 12 million tonnes by 2030, more than 3 times its 2010 level. Now in its 3rd edition, this is the only book which provides a comprehensive review of avocado production, science and technology"--